The Global Jihadist Movement: The Most Lethal Ideology?. Issue 1 (February 2018) - Carson, Jennifer Varriale; Suppenbach, Matthew
Prior research has established a link between ideology and lethality, both within the homicide and terrorism literatures. We examine this relationship as it pertains to the Global Jihadist Movement (GJM). Using a series of logit and negative binomial models with a sample from the Global Terrorism Database, we find that the GJM is indeed more deadly. However, this relationship does not seem to differentially affect Americans, despite their role as the GJM's defined "other."